Association of HLA-DPB1 with Scleroderma and Its Clinical Features in Chinese Population - Wang, Jiucun (Public Library of Science, 2014)
Human leukocyte antigen DPB1 was reported to contain singly nucleotide polymorphisms conferring the strongest susceptibility to systemic sclerosis in Korean population. However, associations of specific DPB1 alleles with SSc vary in different ethnic populations. The aim of this study was to profile DPB1 alleles in Chinese population and to identify specific DPB1 alleles in association with SSc and clinical and serological features of SSc in Han Chinese. A cohort containing 338 patients with SSc and 480 gender-matched and unrelated controls were examined in the study. The HLA-DPB1 genotyping was performed with sequence-based typing method. Exact p-values were obtained (Fisher's test) from 2×2 tables of allele counts or allele carriers and disease status. Thirty eight DPB1 alleles were found in the cohort. DPB1*05:01 was the most common allele in this cohort. DPB1*03:01 and *13:01 were significantly increased in SSc. DPB1*13:01 association had already been described in other ethnic populations, whereas DPB1*03:01 was specific to Han Chinese patients with SSc. In addition, comparisons between SSc subsets indicated that patients carrying DPB1*03:01 were more likely to develop pulmonary fibrosis, DPB1*04 carriers were increased in SSc patients with anti-centromere autoantibodies and in contrast, SSc patients with homozygous DPB1*05:01 showed an opposite association with marginal significance.